Impacts of Eu2+ -doped K3LuSi2O7 phosphor and a scattering particle on conventional white light emitting diodes - Duy, Le Doan; Thai, Nguyen Le; Cong, Pham Hong; Tran, Thinh Cong (Institute of Advanced Engineering and Science, 2024)
The K3LuSi2O7 phosphor doping Eu2+ rare-earth ions (KLS:Eu) was reported to possess broad emission band from near-ultraviolet to nearinfrared. Additionally, this phosphor showed a wide absorption band of 250-600 nm, allowing it to be excited by blue-light chip of 460 nm, making it one of the suitable phosphor materials for a light emitting diode (LED). Besides, the scattering particle material CaCO3 is incorporated into the yellow phosphor layer to serve the scattering-enhancement purpose. The combination of both materials aims at accomplishing improvements in performance of commercial LED package. The concentration of KLS:Eu is constant while that of CaCO3 is modified. As a result, the scattering factor is regulated and become the key factor influencing the optical outputs of the simulated LED. The increasing CaCO3 concentration enhances the phosphor scattering efficiency of light, helping to improve the lumen output and color-temperature consistency of the LED. However, the color rendering performance declines as a function of the CaCO3 growing amount, despite the presence of a KLS:Eu phosphor layer. Further works should be done to optimize the application of KLS:Eu in cooperation with scattering particles for a higher-quality LED device.